ALIH MEDIA KOLEKSI TUGAS AKHIR MAHASISWA PERPUSTAKAAN IAIN MADURA - Nandika Bintan Elhamah (LibTech: Library and Information Science Journal, 2022)
IAIN Madura Library is one of the college libraries that implements uploading theses on the Etheses application. The use of this application supports the library's efforts to display the thesis of a student online so that it can be accessed anywhere and anytime. However, the upload of the Etheses application at the IAIN Madura library began in 2020, so that theses submitted to the library before that year were only in the form of printed files. Obviously, this situation limits the user's ability to access information from a pre existing thesis. Therefore, the IAIN Madura Library carries out the media transfer process for theses that are still in printed form. This media transfer process is also an effort to preserve the value of information contained in existing library materials, prevent loss of information due to damage to library materials, and provide easy access to information for users considering the current rapid technological advances. as a solution to the problem of storing and disseminating information.